Relationship of Anxiety and Depression in Patients with Chronic Periodontitis - Kadkhodazadeh, Mahdi; Abrishami, Mohammadreza; Alam, Mostafa; Shafiei, Shervin; Moslemi, Hamidreza (Journal of Dental School, 2020)
Objectives Many researchers have attempted to link the current concepts of anxiety and depression to periodontal disease. This study aimed to compare the level of anxiety and depression in Iranian patients with chronic periodontitis (CP) and periodontally healthy controls. Methods Fifty CP patients and 50 periodontally healthy controls participated in this study according to our eligibility criteria. Periodontal clinical examination was performed using a Williams probe. The clinical attachment loss (CAL), pocket probing depth (PPD) and bleeding on probing (BOP) were recorded for all teeth except for third molars. In order to psychologically assess the individuals, the Beck’s Depression Inventory (BDI) and the Beck’s Anxiety Inventory (BAI) were used. The mean scores of BAI and BDI were compared between the two groups using the Student t-test. Results The mean age of participants was 44.86±8.07 years. The mean score of BDI was 13.58±8.35 in periodontally healthy controls and 25.62±13.01 in CP patients. The mean score of BAI was 9.9±5.65 in the control and 21.02±13.63 in the test group. The Student t-test revealed a significant difference between the two groups in total score of BDI and BAI (P<0.000). A significant correlation was noted between the BDI and age (P=0.027) but BAI had no significant correlation with age (P=0.245). Conclusion According to the results of this study, the level of anxiety and depression in CP patients was higher than that in periodontally healthy controls in our study population